Measuring HBsAg and HBV DNA Levels in Cilegon - Rolan Sitompul; Martono Roni; Unggul Budihusodo (The Indonesian Society for Digestive Endoscopy, 2009)
Background: Implication of measuring HBsAg level is still not recognized well. The aim of this study to recognize the correlation of serum HBsAg level and serum HBV DNA level between in HBeAg positive patients and HBeAg negative patients. Method: Quantitative serum HBV DNA were collected retrospectively between January 2006 and May 2009. We stratified the patients into four groups, that were; HBeAg positive and (a) ALT 2 x upper limited normal (UNL) (group A),( b) ALT 2 x UNL (group B), HBeAg negative and:( a) ALT 2 x UNL (group C) (b) ALT 2 x UNL (group D). We studied the correlation of serum HBsAg and HBV DNA level in each group. In addition, we also studied the accuracy of HBsAg titers to predict serum HBV DNA levels in each group by using receiver operating characteristic (ROC) curve analysis. Results: Eighty nine patients were recruited in this study. Most of them 63 (70%) were male; the mean age of the patients was 38.49 ± 11.21 years. The number of patients with HBeAg positive and negative were 28 and 61 respectively. Based on the group stratification, the A, B, C and D groups we found 16, 12, 11, 50 respectively. There was a positive correlation between HBsAg titers and HBV DNA level in HBeAg positive patients but it was statistically not significant. Similar result was also found in HBeAg negative patients. There were positive correlation in group A, C, and D but they were not statistically significant. In group B the correlation was negative (r = -0.40). We found 100% sensitivity and 100% specificity of predicting serum HBV DNA levels in group A with HBsAg cut-off level of 7.91 IU/mL and baseline serum HBV DNA cut-off level 20,000 IU/mL. In group B, C and D the accuracy to predict serum HBV DNA level were not so good . Conclusion: There were positive correlation between HBsAg titers and HBV DNA levels in HBeAg positive and HBeAg negative patients as demonstrated in the three group stratification; however, the correlation was negative in group HBeAg positive and ALT 2 x UNL. We found excellent (100%) specificity and sensitivity for predicting serum HBV DNA level in group HBeAg positive and ALT 2 x UNL with HBsAg cut-off level 7.91 IU/mL and baseline serum HBV DNA cut-off level 20,000 IU/mL; while in other groups, the correlation were not so good. Keywords: serum HBsAg level, serum HBV DNA level, hepatitis B, correlation